How adolescents perceive their future, and why: a cross-cultural study - Grootboom, Gregory Allen (University of the Free State, 2007)
After the change to full democracy in 1994, South African society had to transform. Education was seen as the platform from which this transformation was to be launched. This transformation of education however, had differential impacts on the future time perspective of learners in secondary schools. The purpose of this study was to determine how learners perceived their futures; to determine whether there were cross-cultural differences and what the factors were that impacted on the future time perspectives of learners. The research followed a mixed method approach, with the participation of 395 learners from different schools in the Northern Cape, South Africa. For the quantitative study the Future Time Perspective measure and the Repertory Grid were used and for the qualitative part, a self designed open-ended questionnaire was employed. The results showed that the different cultures perceived their futures differently, with the Black and Coloured groups having a shorter time perspective than the White group. The society in which the school functions also has differential impacts on learners. All learners saw violence as having the biggest impact on their possible selves. Learners demonstrated similarities as well as differences in some areas. The Tswana and Xhosa learners cited health concerns and gangsterism (crime) as negatively impacting factors. Coloured learners focused on gangsterism and racism, whereas White learners saw racism and social justice issues impacting on their futures. Having noted that racism, violence and health concerns as the greatest threat to learners’ future time perspective, the researcher provided a praxis through which educators can deracialise. Guidelines were also suggested as a challenge to education so that these societal issues may be addressed in the school. Challenges for future research in the field of identity formation after such rapid social transformation have to be undertaken. A new term, second racism, could be explored further. Additionally, the constitutional mandates which afford more opportunities for the female child could also impact on the identity development, as well as the possible selves of the female learner.
Thesis (Ph.D. (Psychology of Education))--University of the Free State, 2007
Keywords: Time perspective in adolescence; Cross-cultural studies -- South Africa -- Northern Cape; Identity (Psychology) in adolescence; Ethnicity; Multicultural education; Racism; New racism; Second racism; Possible selves; Cultural capital; Culture